A theoretical analysis of the energy rebound effects of private consumers. (November 2021) - Wang, Jiayu; Xing, Xinpeng; Liu, Yufei; Zhu, Yu; Liu, Tiansen
Abstract: The research uses microeconomic theory and consumer theory to analytically test the theoretical basis of the indirect rebound effect caused due to upsurge in the energy efficiency of consumers from the private sector. It also explains how to use the carbon dioxide emissions reflected in the life cycle assessment to forecast and describes the indirect rebound effect of carbon dioxide emissions measured by the household sector. In addition, the thesis also empirically benefits the research studies focused on the rebound effect as it stimulates the policy scenarios and BAU in an estimated common equilibrium framework. According to the theoretical studies, there are different elasticities for the firm and household that determine the extent of the rebound effect and these determinants vary as the policy standards turn further stringent. Moreover, it is also shown that each of these policy scenarios exerts a much large rebound effect that outspreads throughout the economy, reaching up to half of the entire economy being measured by the life cycle of greenhouse emissions. Though more direct rebound effects are generated from the stringent fuel efficiency standard which is measured in terms of the higher percentage than the medium and lenient standards but still more decrease in the carbon emissions is attributed to the stringent policy that is measured in terms of the physical units.